2017
DOI: 10.3329/bjmm.v9i2.31414
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of multidrug resistant and extensively drug resistant community acquired uropathogens in Dhaka city, Bangladesh.

Abstract: Because of indiscriminate, inadequate and irrational usage of antimicriobials, the sensitivity pattern of community acquired uropathogens is changing drastically, specifically in developing countries, such as Bangladesh. This study was undertaken to investigate the profile of common uropathogens in community settings and to evaluate their antimicrobial resistance profile in order to categorize them into multidrug resistant (MDR), extensively drug resistant (XDR) and pandrug resistant (PDR) organisms.Total 800 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…More MDR and XDR strains in E. coli than K. pneumoniae in our study could be due to the fact that the number of E. coli strains isolated were more than K. pneumoniae. In regard to XDR and PDR, the current study is supported by the findings of previous studies [30, 31] however our finding strongly disagree with a study conducted by Ahmed Hasanin et al [32] in the prevalence of XDR strains of FGNB. In this study lower XDR E. coli (18%) and K. pneumonia (11%) were reported as compared to the previous study where higher XDR K. pneumoniae (52%), and E. coli (47%) were reported [32].…”
Section: Discussionsupporting
confidence: 53%
“…More MDR and XDR strains in E. coli than K. pneumoniae in our study could be due to the fact that the number of E. coli strains isolated were more than K. pneumoniae. In regard to XDR and PDR, the current study is supported by the findings of previous studies [30, 31] however our finding strongly disagree with a study conducted by Ahmed Hasanin et al [32] in the prevalence of XDR strains of FGNB. In this study lower XDR E. coli (18%) and K. pneumonia (11%) were reported as compared to the previous study where higher XDR K. pneumoniae (52%), and E. coli (47%) were reported [32].…”
Section: Discussionsupporting
confidence: 53%
“…The selection of appropriate antibiotics is crucial for the treatment of infection and therefore analysis of the bacterial susceptibility pattern is helpful in this context.The objective of our study was to analyze antibiotic susceptibility pattern of [12][13][14][15], India (susceptibile 50% to 80%) [16], and Nepal (susceptibile 87.8% to 95.3%) [17] also reported carbapenem as the most effective antibiotic against Enterobacteriaceae.…”
Section: Discussionmentioning
confidence: 99%
“…In India, the frequency of MDR strains was reported as 75% [20], while in South Korea, it was 21.9% [21]. A study in Bangladesh in 2015 reported a prevalence of 70.67% MDR E. coli isolates and 14% XDR isolates, although no PDR isolates were detected [22]. In Iraq, a recent study conducted in 2023 reported a prevalence of XDR isolates at 21.24% and PDR isolates at 1.77% [23].…”
Section: Fig 1 Comparison Of Mean Absorbance At 570 Nm In Drug-resist...mentioning
confidence: 99%